International adjudication and autonomy - Merrills, John (International Organizations and the Idea of Autonomy, 2011)
In a project concerned with the idea of international organizations as autonomous entities it is natural enough to find courts and tribunals receiving their fair share of attention. Not only are international judicial institutions of various kinds now increasingly numerous but autonomy, as we shall see, can be regarded as one of the key features of adjudication internationally, as well as in the domestic arena. Autonomy is therefore well worth examining in this context. But what exactly do we mean by judicial autonomy? How is it manifested and what are its limitations? These questions are the subject of this chapter.